PROSEDUR PENGUJIAN TANAH UNTUK BEBERAPA DAERAH DI JAWA BARAT - Sunaryo, Bemby
Index tests for some tropical soils in West Java have been carried out. Disturbed samples were obtained from three location (Purwakarta, Cikampek, and Bandung) and tested to find the effect of drying/wetting on moisture content, Atterberg limits, particle size distribution, and compaction characteristics. An additional sample was taken from Lembang and tested to find the effect of drying on moisture content and compaction characteristics. Laboratory tests were carried out using standard and modified procedures. The British Standard methods were applied to almost all of the laboratory testing, the modifications applied being those which distinguish the characteristics of tropical soils compared with conventional temperate soils for which standard testing procedures have been devised. From the comprehensive laboratory test programme it was found that there were some significant differences between results obtained using standard procedures compared with the modification applied. Comparison was also made with earlier work conducted in the 1970's. The effect of drying on tropical residual soils was found to decrease liquid limits, the plasticity index, and the percentage passing in the hydrometer test. Optimum moisture content in compaction testing was lowered with corresponding increase in maximum dry density. Engineering characteristics were examined using index test results and it was found that the effect of drying on tropical residual soils could make some difficulties in the prediction of likely engineering performance involving these soils.